Love Hurts?: Identifying Abuse in the Virgin-Beast Trope of Popular Romantic Fiction - Maas, Megan K. (Journal of family violence, 2021)
Popular romantic fiction dating back to the 1700s often portrays a submissive/virginal female character and an aggressive/beastly male character. This binary portrayal of heterosexual relationships is problematic because it presents a power imbalance within the couple as essential for romance. Although several scholars have described this phenomenon, it has yet to be named and applied to violence prevention work. In response, the purpose of this study is to develop the term “virgin-beast trope” to capture this relationship dynamic and situate this concept within the larger body of relationship violence research. We use three of the most popular romantic fiction films (Beauty and the Beast, Twilight, and Fifty Shades of Grey) to illustrate the virgin-beast trope and demonstrate its continuity from childhood to adulthood. We then use the Abuse Litmus Test to identify examples of relationship abuse embedded within the virgin-beast trope as evidenced in these films. Although unhealthy features of these three relationships are often masked in romanticization, the inherent disproportional power dynamic of the virgin-beast trope results in the male partners using their ‘beastly power’ through threats, intimidation, isolation, and stalking to control the subordinate and virginal female partner. In response, the female partners try to ‘tame the beast’, but ultimately suffer harm as a result. The prominent virgin-beast trope across romantic fiction could be added to existing media literacy education to support more engaging conversations that address relationship violence prevention across developmental stages.